Optimalisasi Potensi Desa Seketi Melalui Inovasi Pembuatan Pie Susu Jahe - Slamet Fauzan; Diani Feralia Rahmadani; Winda Aulia; Linda Shinta Devi; Qurrota Akyun (FEB-UP Press, 2020)
Seketi Village is a village located in Mojoagung Subdistrict, Jombang Regency, East Java, which has potential plants including toga plants including red ginger. Red ginger cultivation in Seketi Village is only processed into a red ginger powder. Processed consists of red ginger powder which is sold by the public but is limited because not everything is offered. The purpose of this community service program is to educate rural communities through training in making red ginger culinary preparations namely red ginger milk pie. The research method used is direct training by documenting each of the steps practiced in the process of making red ginger milk pie. Furthermore, the recording was uploaded to the Seketi Village YouTube account. The results obtained from this community service activity are the creation of processed red ginger in the form of red ginger milk pie.